Transcranial Magnetic Stimulation Reveals Executive Control Dissociation in the Rostral Prefrontal Cortex - He, Weijiang; Fan, Chenggui; Li, Ling (Frontiers in Human Neuroscience, 2017)
Although previous studies have shown that the rostral prefrontal cortex (rPFC) plays a crucial role in executive tasks, the various functions of the rPFC in the human are still understudied. Here we used transcranial magnetic stimulation (TMS) with continuous theta burst stimulation (cTBS) to interfere with the executive control functions of the right rostrolateral PFC (RLPFC) or the right rostromedial PFC (RMPFC). Subjects performed a task-switching paradigm, which included spatial detection (SD), prospective memory (PM), and working memory (WM) tasks, after cTBS. The performance of eighteen healthy volunteers was evaluated on different days after cTBS over the right RLPFC, the right RMPFC, and the vertex (serving as a control site). The application of cTBS over the RLPFC significantly increased the switching costs (SCs) of the error rates (ERs) when switching to the PM task, while RMPFC-cTBS decreased SCs of ERs when switching to the WM task, compared with the control vertex site. These findings provide evidence for a differential role of the RLPFC and the RMPFC in executive functions, with a specific involvement of the RLPFC and the RMPFC in PM, and WM, respectively.